Trade Openness, Exchange Rate Volatility and Export Performance in Nepal - Rana, Surya Bahadur; Baniya, Sweta; Khanal, Anisha; Bhusal, Nisha; Pandey, Nisha; Subedi, Asmita; Shrestha, Anisha (Kshitiz Management Review, 2026)
This paper analyzes the long-run relationship among trade openness, exchange rate volatility, and export performance in Nepal using the ARDL bounds testing approach for the period 1979–2024. The results of unit root test reveals that the variables are integrated either at order zero or at order one or at the combination of both, validating the applicability of the ARDL model. The ARDL bounds test reveals the existence of a stable long-run relationship among trade openness, exchange rate volatility, the real exchange rate, inflation, and export performance. The results of long-run estimation show that trade openness has a significant positive effect on export performance in Nepal, indicating that greater integration into the global economy enhances export growth and competitiveness. In contrast, exchange rate volatility, the real exchange rate, and inflation do not exhibit significant long-run effects on export performance. The error correction model indicates that short-run disequilibrium adjusts toward long-run equilibrium at a moderate speed of 27.97 percent annually. The study recommends promoting trade openness, export diversification, and exchange rate stability to strengthen Nepal’s export performance and international competitiveness.